The Changing Profile of The College of The Bahamas’ Graduates - Fielding, William J.; Gibson, Jeannie (International Journal of Bahamian Studies, 2014)
This paper uses graduation data to show the changes that have occurred in the profile of the College’s graduates from 1976 to 2013. The data demonstrate the rise and fall in the number of graduates receiving Associate degrees. The decline in the number of graduates obtaining Associate degrees can be connected with the rise in the number of graduates receiving Baccalaureate degrees. While College to University: Strategic Plan, 2009-2019 of the College of The Bahamas considers the College era to be associated with two phases, “Creation and Early Growth: The College of The Bahamas, 1974-1995” and the “Transition Era: From College to University, 1995-2009”; the graduation data show a complex and ongoing picture of change, consolidation and change.